2018
DOI: 10.1016/j.mehy.2018.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Inducing hypertrophic effects of type I skeletal muscle fibers: A hypothetical role of time under load in resistance training aimed at muscular hypertrophy

Abstract: An emerging body of evidence is starting to suggest that the hypertrophy of skeletal muscle fibers might be load specific. In other words, it may be that resistance training with high loads (i.e., ≥60% of 1 repetition maximum [RM]) emphasizes a greater growth of type II muscle fibers, while resistance training with low loads (i.e., <60% of 1RM) might primarily augment hypertrophy of type I muscle fibers. Type I and type II muscle fibers possess certain distinct characteristics, with type II muscle fibers havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 32 publications
0
20
0
1
Order By: Relevance
“…Therefore, the CB during the bench press exercise could allow the bar to be accelerated through a greater ROM, which might result in significantly higher bar velocity and power output compared to an SB. Furthermore, the changes in ROM during the resistance exercise can also impact the time under tension or recently used -term time under load (TUL) (Grgic et al, 2018) in a particular set, as well as in a whole training session. A common method of measuring resistance training volume is multiplying the repetitions with the external load (Padulo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the CB during the bench press exercise could allow the bar to be accelerated through a greater ROM, which might result in significantly higher bar velocity and power output compared to an SB. Furthermore, the changes in ROM during the resistance exercise can also impact the time under tension or recently used -term time under load (TUL) (Grgic et al, 2018) in a particular set, as well as in a whole training session. A common method of measuring resistance training volume is multiplying the repetitions with the external load (Padulo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…While the meta-analysis of Schoenfeld et al ( 2017 ) reported similar changes in muscle size irrespective of loading schemes, the question remains as to whether the hypertrophy of type I and type II muscle fibers was also similar between high- and low-load conditions. It might be that high-load RT emphasizes type II muscle hypertrophy (Campos et al, 2002 ), with low-load RT stimulating greater growth in type I muscle fibers (Ogborn and Schoenfeld, 2014 ; Grgic et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such improvements have also been observed in spite of a reduction of the sportspecific training volume [17,18]. Moreover, high-intensity strength training favors greater muscle power, mainly via neural adaptations, with no or very little hypertrophic response [14], while resistance training with low loads (i.e., <60% of 1RM) might primarily augment the hypertrophy of type I muscle fibers, which have a higher oxidative capacity and a higher fatigue threshold [19]. Give that muscle hypertrophy could have a negative impact on weight-bearing endurance events, the muscle hypertrophy protocol was not adopted in our study.…”
Section: Discussionmentioning
confidence: 99%